BRIOFITLARDAN ATROF-MUHITNI BIOMONITORING QILISHDA FOYDALANISH (Journal of Science-Innovative Research in Uzbekistan, 2024)
The level of air and soil pollution with heavy metals and radionuclides has increased significantly over the past decades. Since radionuclides can be transportedover long distances from the source along with air masses and accumulate in the environment during fallout, their negative consequences may not appear immediately,but over time. The article presents the results of the study of scientific sources and research results. For this, the use of bryophytes as a biological object and monitoring system is suitable